Obtaining strength-ductility combination in a laser additive manufactured (FeCoNi)86Al7Ti7 high-entropy alloy at cryogenic temperature - Kaiqiang Xie; Yacheng Fang; Pan Ma; Hong Yang; Shiguang Wan; Konda Gokuldoss Prashanth; Piter Gargarella; Yongkun Mu; Gang Wang; Yandong Jia (Journal of Materials Research and Technology)
High-entropy alloys (HEAs) are known for their distinctive microstructural features, outstanding performance, and potential applications, establishing them as novel metallic materials. Studies indicate that face-centered cubic HEAs generally offer increased strength and toughness at lower temperatures, suitable for cryogenic applications. This work on (FeCoNi)86Al7Ti7 HEA fabricated using powder bed fusion (PBF) studies the phase composition, microstructure, and mechanical properties at both room and cryogenic temperatures (298 K and 77 K). The PBF HEA exhibits a hierarchical microstructure with columnar grains, Ti-enriched cellular substructures entangled with high-density dislocations, and L21 nanoprecipitates, contributing to an excellent strength-ductility combination at room temperature. Notably, as the temperature decreases from 298 K to 77 K, both strength and ductility increase, with a higher yield strength of ∼1.0 GPa, ultimate tensile strength of ∼1.55 GPa, and ductility of ∼42%. Dislocation strengthening is dominant at both room and cryogenic temperatures, with dislocation slip as the primary deformation mechanism at 298 K and a combination of dislocation slips and stacking faults at 77 K.